Self-efficacy of high-performance volleyball athletes - do Amaral Machado, Thais; Vieira do Nascimento, Juarez; Juliana Paes, Mayara; Jungles Fernandes, Gabriel; da Silva Lirani, Luciana; Facco Stefanello, Joice Mara (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Self-efficacy determines the regulation of athletes' thinking patterns and how they will behave to achieve their goals in the face of adversity. The aim of this study was to analyze the relationship between volleyball self-efficacy and the performance efficacy of athletes from high-performance teams at distinct moments of the season. This descriptive correlational study included sixty-five athletes of both sexes (26.20 ± 5.51 years old) from four teams competing in the 2017/2018 Men's and Women's Superliga. The Volleyball Self-Efficacy Scale (VSES) measured athletes' self-efficacy, and notational analysis evaluated the efficacy of volleyball performance. The results showed strong or very strong self-efficacy in the game, defensive self-efficacy, offensive self-efficacy, and global self-efficacy, as well as relationships between defensive self-efficacy and defensive efficacy, and between offensive self-efficacy and offensive efficacy. The high-performance athletes across both variables investigated were partially susceptible to circumstantial issues inherent to the sport context, such as matches inside or outside home, with public for or against, with teams of different technical levels, with teams that have a history of confrontations with more wins or more defeats against their team.